(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2017)
A new larger benthic foraminifer, Asterigerina cayrazensis n. sp., is described from the upper Ypresian (middle-upper Cuisian) of the Çayraz section, N of Haymana, S Ankara, central Turkey, from which also the rotaliine species Ornatorotalia spinosa, O. granum and Granorotalia sublobata are first recorded. In addition, Ornatorotalia sp. is recorded from the Thanetian limestone of the Harabekayış section, W Elazığ, eastern Turkey.